An ultrastable perovskite–polymer exciplex through self energy-level adaption for under-water light-emitting devices. Issue 22 (19th May 2022) - Zhang, Yiwei; Zhang, Baohuan; Fu, Yulan; Han, Yu; Zhang, Tinglin; Zhang, Lisha; Guo, Jinxin; Zhang, Xinping
Abstract : A light emitting polymer and perovskite composite in the matrix of a photo polymerized polymer is reported. The material shows photoluminescence from exciplex of emitting polymer and perovskite, and superb water-repellent property is determined. Abstract : Light-emitting lead halide perovskite materials have attracted great attention due to their excellent optoelectrical properties. However, the combination of perovskites and conjugated polymers forming an exciplex has not been reported due to the limitations of fabrication. In this work, we introduce a strategy by using an ultraviolet (UV)-polymerizable acrylic monomer to fabricate perovskite–polymer composite films in the polymer matrix. Significantly, we systematically examined the exciton dynamics in composite films by time resolved photoluminescence and transient absorption spectra. We observed the formation of an exciplex and the emission from it. The energy levels and exciton dynamics of perovskite light-emitting polymers in the composite is proved to be influenced by the photopolymer matrix and the energy levels in the polymer matrix make the charge transfer and exciplex formation feasible. Furthermore, light-emitting devices were fabricated using the composite materials as phosphors on a 395 nm UV chip. The devices illustrate excellent water-repellent properties, which can work in an aqueous atmosphere for a long time. This method provides a facile strategy for the preparation of ultrastable composites employing both perovskites and light-emitting polymers and deepens our understanding of the exciton dynamics in such composite materials. It is beneficial for the development of next-generation light-emitting devices and displays.